Arabic Greeting Variations in Surakarta (Sociolinguistic Studies) - Hesti Indah Mifta Nur’aini; St Y Slamet; Budhi Setiawan (Universitas Indraprasta PGRI, 2018)
This study aims to describe the variation of the greeting words used by Arabians in Surakarta. This study used descriptive qualitative method. The data in this research is the speech language used by the Arab ethnic community in Kecamatan Pasar Kliwon, Surakarta by searching for linguistic features on the variation of the word greeting. Sources of data were obtained from informants who were Arabs in Surakarta. Technique of data analysis using technique of padan. Based on analysis results can be concluded that the variation of Arabic greeting of Arabian community in Surakarta has its own peculiarities. Such distinctiveness is indicated through the greetings associated with pronouns, kinship, social status, and professions used by Arabs more still influenced by the Arabic element. Nevertheless, some of the greetings have shifted in Indonesian and Javanese.